Comparison of 12- and 16-Core Prostate Biopsy in Japanese Patients with Serum Prostate- Specific Antigen Level of 4.0-20.0 ng/mL - Miyoshi, Yasuhide; Furuya, Masahiro; Teranishi, Jun-ichi; Noguchi, Kazumi; Uemura, Hiroji; Yokomizo, Yumiko; Sugiura, Shinpei; Kubota, Yoshinobu (Urology Journal, 2014)
Abstract Purpose: In the present study, we compared 12- with 16-core biopsy in patients with prostate- specific antigen (PSA) levels of 4.0-20.0 ng/mL. Materials and Methods: Between 2003 and 2010, 332 patients whose serum PSA level was between 4.0 and 20.0 ng/mL underwent initial transrectal ultrasound (TRUS)-guided needle biopsy. Of those patients, 195 underwent 12-core biopsy and 137 underwent 16-core biopsy. Results: In the 12-core prostate biopsy group, 66 (33.8%) patients were found to have prostate cancer. On the other hand, in the 16-core prostate biopsy group of 137 patients, 61 (44.5%) were found to have prostate cancer. Among all patients, the prostate cancer detection rate was slightly higher in the 16-core biopsy group than in the 12-core biopsy group. Moreover, in patients with prostate volume > 30 mL or PSA density (PSAD) < 0.2, the prostate cancer detection rate was significantly higher in the 16-core biopsy group than in the 12-core biopsy group. There was no significant difference in pathological tumor grade, indolent cancer probability, or biopsy complication rate between the two groups. Conclusion: In order to detect prostate cancer, 16-core prostate biopsy is safe and feasible for Japanese patients with serum PSA level of 4.0-20.0 ng/mL.